Exploring school choice and the consequences for student racial segregation within Pennsylvania's charter school transfers - Erica Frankenberg; Stephen Kotok; Kai Schafft; Bryan Mann (Arizona State University, 2017)
Using individual-level student data from Pennsylvania, this study explores the extent to which charter school racial composition may be an important factor in students' self-segregative school choices. Findings indicate that, holding distance and enrollment constant, Black and Latino students are strongly averse to moving to charter schools with higher percentages of White students. Conversely, White students are more likely to enroll in such charter schools. As the percentage and number of students transferring into charter schools increases, self-segregative school choices raise critical questions regarding educational equity, and the effects of educational reform and school choice policies on the fostering of racially diverse educational environments.